EFFECTS OF TEACHERS’ GENDER AND QUALIFICATION ON STUDENTS’ PERFORMANCE IN VOCATIONAL TECHNICAL EDUCATION - Igberadja, Serumu (Journal of Technical Education and Training, 2016)
The purpose of this study was to assess the effects of teachers’ gender and qualification on students’ performance in industrial safety. Two research questions guided the study and 2 hypotheses were tested at 0.05 level of significance. Ex-post facto research design was used and the population of the study was 334 students who registered Industrial Safety (TED 112) from 2004/2005 to 2013/2014 Academic Session. Due to the results TED112 available at the time of request for TED112 results, purposive sampling technique was used to select the TED112 result of students for 4 sessions. Two sessions each was selected based on the lecturers’ gender and qualification. However, 2007/2008, 2008/2009, 2009/2010, and 2013/2014 Session results were used as sample of the study. Therefore, the sample of the study was 91 undergraduate students. No instrument was developed in this study rather a letter was used to request for data. Data collected was analysed using mean for the research questions and anova (Analysis of variance) to test the hypotheses. The result revealed that the teachers’ gender and qualification do not have any significant effects on students’ performance in Industrial Safety. Hence, it was recommended among others that Delta State Ministry of Higher Education should employ qualified male and female lecturers to teach vocational technical education courses, since students’ performce is not related to the gender and qualification of the teacher, there should be no gender and qualification preference in recruiting VTE teachers in schools.